Technical note: Development of Hemipyrellia ligurriens (Wiedemann) (Diptera: Calliphoridae) at constant temperatures: Applications in estimating postmortem interval. (August 2015) - Yang, Yong-qiang; Lyu, Zhou; Li, Xue-bo; Li, Kui; Yao, Lan; Wan, Li-hua
Highlights: This study reports the developmental times for H. Ligurriens from 16 to 34 °C . Three developmental models are constructed and are ready for estimate PMImin . The t and the K for the each developmental stage of H. ligurriens are obtained. The range of 16 to 28 °C is considered optimal for the development of H. ligurriens . Abstract: Blowflies (Calliphoridae) are recognized as a powerful tool for estimating the minimum postmortem interval (PMImin ). The times for blowflies to develop from oviposition to eclosion is mainly controlled by temperature, which can differ between even closely related species. Hemipyrellia ligurriens (Wiedemann) (Diptera: Calliphoridae) is a blowfly distributed throughout Asia and Australia. However, a systematic determination of the developmental times of H. ligurriens under constant temperature, necessary for estimating the PMImin, is lacking. Such an examination would broaden the forensic importance of the species. Thus, this study explored the growth curves of larval H. ligurriens at 7 constant temperatures (16, 19, 22, 25, 28, 31, and 34 °C). Isomegalen and isomorphen diagrams were successfully constructed, depicting the time of larval length or developmental event, respectively, at different temperatures. A thermal summation model was also constructed via regression analysis, by estimating the developmental threshold temperature t and thermal summation constant K . The thermal summation model indicated that t at 8.3 °C and K at 5747.5 degree-hours (°C h) are required for complete development from oviposition to eclosion, and suggested an optimum temperature range of 16–28 °C for the development of H. ligurriens . These data establish for the first time the temperature-dependent developmental time of H. ligurriens for forensic entomology application. The 3 developmental models are provided.